EPISTEMOLOGI KEILMUAN PENDIDIKAN ISLAM DI PESANTREN SALAFIYAH BAHRUL ULUM SIMO BOYOLALI - Abdullah Abdullah; Mujiburrohman Mujiburrohman (STKIP Pesisir Selatan, 2025)
This study aims to examine the epistemology of Islamic education knowledge at Bahrul Ulum Salafiyah Pesantren (Simo, Boyolali), focusing on how sources of knowledge (revelation, reason, textual tradition, and pedagogical experience) are positioned, integrated, and validated in learning practices. A qualitative case study design was employed. Data were collected through in-depth interviews and source triangulation involving two teachers (Muhammad Ali Rohmatullah and Muhammad Umar Al-Faruq) and one alumnus (Muhammad Usman Al-Ghoni), followed by thematic analysis. The findings indicate that revelation functions as the axiological horizon and educational purpose, the mu‘tabar textual tradition (classical Islamic texts) serves as the primary reference, reason operates as an instrumental faculty within the boundaries of tradition, and pedagogical experience becomes an internalization mechanism through bandongan, sorogan, and repetition (takrīr). Knowledge validation is established through a layered chain of legitimacy: textual accuracy, teacher verification (tashih), and reinforcement through authoritative scholarly references. These patterns align with al-Ghazali’s ethical-spiritual orientation of knowledge, al-Attas’s concept of ta’dib as the core of education, and Ibn Khaldun’s principles of gradualism and repetition (tadrīj–takrīr) in forming stable competencies (malakah). The study implies that pesantren learning design should strengthen authoritative references and adab while directing reason constructively to sustain a coherent and productive integration of knowledge.